Preliminary evaluation of surface dielectric barrier discharge non-thermal plasma for reforming syngas derived from a downdraft gasifier. (15th January 2023) - Indrawan, Natarianto; Plotnikov, Viacheslav; Thapa, Sunil; Diaz, Gerardo C.; Kumar, Ajay; Huhnke, Raymond L.
Highlights: Syngas derived from a downdraft gasifier was reformed using non-thermal plasma. An increase in hydrogen content from 4.8 to 9.5 vol.% was observed. Syngas tar decreased by 88 %, from 25 to 3 g/Nm 3. Energy density for operating the plasma system was observed at 0.19 kWh/m 3. This study can be a basis for clean hydrogen production and tar abatement systems. Abstract: Measurement by NASA has indicated an increase in carbon dioxide levels in the air from 381 to 417 ppm from 2006 to 2022. Gasification is a proven technology that can reduce carbon accumulations in the air as it can convert renewable organic materials into syngas, including hydrogen as future clean energy fuel, and sequester carbon in the form of biochar. However, tar in syngas still remains a challenge, requiring complex gas cleaning system. This study presents a critical evaluation of reforming syngas directly from a gasifier for increased hydrogen (H2 ) production while reducing syngas tar using dielectric barrier discharge (DBD) plasma. Results showed an increase in H2 (from 4.8 to 9.5 vol%) with a slight increase in CO (from 31.9 to 34.7 % vol.%) and a decrease in heavier hydrocarbons, such as C2 H6 (from 8.5 to 4.6 vol%). Syngas tar decreased by 88 %, from 25 to 3 g/Nm 3 . At steady-state operation, the power consumption for operating the plasma system was 160 W, resulting in energy density of 0.19 kWh/m 3 . The outcome of this study is critical for further development of existing gasification systems capable of treating diverse organic feed streams, including biomass, coal, municipal solid waste (MSW), and plastic.